Composite catalyst, preparation method and application thereof, and method for preparing DMF (Dimethyl Formamide)

By using molecular sieve to embed composite catalysts containing copper particles, the problem of short catalytic life of existing catalysts in the preparation of DMF by hydrogenation of CO2 is solved, and the catalytic life is significantly improved and catalytic stability is achieved.

CN119488940APending Publication Date: 2025-02-21LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311040261.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing phosphine-containing polymer-supported ruthenium catalysts have a short catalytic life in the preparation of DMFs with catalytic CO2 hydrogenation, which is difficult to meet the continuous operation needs of industrial production.

Method used

A composite catalyst is used, which consists of a molecular sieve and copper-containing particles embedded in the molecular sieve. The copper-containing particles include copper metal particles and copper oxide particles. Through specific preparation methods, including sol-gel method and hydrothermal crystallization, composite catalysts with long catalytic life are prepared.

Benefits of technology

This composite catalyst exhibits a long catalytic life in the preparation of DMF by catalytic CO2 hydrogenation, can run continuously for more than 500 hours, and maintains good selectivity and yield, solving the problem of short life of existing catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488940A_ABST
    Figure CN119488940A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and particularly relates to a composite catalyst, a preparation method and application thereof, and a method for preparing DMF (Dimethyl Formamide). The invention provides a composite catalyst which comprises a molecular sieve and copper-containing particles embedded in the molecular sieve, and the copper-containing particles comprise copper metal particles and cuprous oxide particles. When the catalyst provided by the invention is used for catalyzing CO2 hydrogenation to prepare DMF, relatively high selectivity and yield are achieved, and the composite catalyst provided by the invention has excellent catalytic stability and still has good selectivity and yield after continuous catalytic operation for 500h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a composite catalyst and a preparation method and application thereof, and a method for preparing DMF. Background Art

[0002] N,N-dimethylformamide (DMF) is an important organic chemical intermediate, which is widely used in the synthesis of pesticides, dyes, fragrances, etc. At present, the industrial production route of DMF is mainly to generate DMF by direct reaction of dimethylamine and carbon monoxide catalyzed by sodium methoxide. Although this production method has the advantages of wide source of raw materials and suitable for large-scale continuous production, it also faces the following problems in actual production: 1) anhydrous dimethylamine is required as raw material, which has strict requirements on raw materials; 2) this method still relies on non-renewable coal resources (using coal resources to prepare carbon monoxide), which is not conducive to sustainable development.

[0003] In order to overcome the defects of preparing DMF in the prior art, researchers studied the use of CO2 and H2 as formylation agents and amines for catalytic reaction to prepare DMF; CO2 is a cheap, non-toxic and renewable C1 resource, and H2 is the cleanest reducing agent. For example, the document "An Efficient and Practical System for the Synthesis of N,N-Dimethylformamide by CO2 Hydrogenation using a Heterogeneous Ru Catalyst: From Batch to Continuous Flow" (ChemSusChem 2020, 13, 1735-1739) discloses a method for preparing formamide compounds by hydrogenation of CO2 catalyzed by a phosphine-containing polymer-supported ruthenium catalyst, and it was continuously operated in a fixed bed for 60 hours. However, the catalytic life of the existing phosphine-containing polymer-supported ruthenium catalyst in catalyzing CO2 hydrogenation to prepare DMF is relatively short, mostly less than 100 hours. Summary of the invention

[0004] In view of this, the present invention provides a composite catalyst and its preparation method and application, and a method for preparing DMF. The composite catalyst provided by the present invention has a long catalytic life in catalyzing CO2 hydrogenation to prepare DMF and can operate continuously for 500 hours.

[0005] In order to solve the above technical problems, the present invention provides a composite catalyst, comprising a molecular sieve and copper-containing particles embedded in the molecular sieve, wherein the copper-containing particles include copper metal particles and cuprous oxide particles.

[0006] Preferably, the mass percentage of the copper-containing particles in the composite catalyst is 2-15%.

[0007] Preferably, the silicon to aluminum ratio of the molecular sieve is 20 to 100:1.

[0008] The present invention also provides a method for preparing the composite catalyst described in the above technical solution, comprising the following steps:

[0009] Mixing a copper-based metal organic framework compound, a silicon source and a first solvent to obtain a sol-gel;

[0010] The sol-gel is aged and then dried to obtain a MOF / SiO2 composite;

[0011] The MOF / SiO2 composite, aluminum source, template, alkaline substance and second solvent are mixed and then subjected to hydrothermal crystallization, calcination and reduction treatment in sequence to obtain the composite catalyst.

[0012] Preferably, the copper-based metal organic framework compound is a Cu3(BTC)2 metal organic framework compound;

[0013] The silicon source includes organic silicate, silica sol, water glass or white carbon black;

[0014] The mass ratio of the copper-based metal organic framework compound to the silicon source is 1:3-26;

[0015] The first solvent is a mixed solvent of water and an organic solvent, and the mass ratio of water to the organic solvent is 1:1-4;

[0016] The mass ratio of the copper-based metal organic framework compound to water is 15 to 60:100;

[0017] The mixing temperature is 45-85° C. and the mixing time is 1-3 hours.

[0018] Preferably, the aging time is 12 to 30 hours;

[0019] The drying is oven drying, the oven drying temperature is 80 to 140° C., and the oven drying time is 2 to 12 hours.

[0020] Preferably, the aluminum source is Al(NO3)3·9H2O, pseudo-boehmite, aluminum sulfate or sodium aluminate; the mass ratio of the aluminum source to SiO2 in the MOF / SiO2 composite is 1:5-10;

[0021] The template agent is tetrapropylammonium hydroxide, tetrapropylammonium chloride, tetraethylammonium hydroxide or tetrabutylammonium hydroxide; the mass ratio of the aluminum source to the template agent is 1:5-10;

[0022] The alkaline substance is ammonia monohydrate;

[0023] The second solvent is a mixed solvent of ethanol and water; the mass ratio of the ethanol to water is 40-80:50-100.

[0024] Preferably, the hydrothermal crystallization temperature is 150-200°C and the time is 1-5 days;

[0025] The calcination temperature is 500-650°C and the calcination time is 1-5h;

[0026] The reduction treatment is to carry out a reduction reaction in a reducing atmosphere; the temperature of the reduction reaction is 300 to 550° C., and the time of the reduction reaction is 2 to 5 hours.

[0027] The present invention also provides the use of the composite catalyst described in the above technical solution or the composite catalyst prepared by the preparation method described in the above technical solution in catalyzing CO2 hydrogenation to prepare DMF.

[0028] The present invention also provides a method for preparing DMF by catalyzing CO2 hydrogenation using the composite catalyst described in the above technical solution or the composite catalyst prepared by the preparation method described in the above technical solution, comprising the following steps:

[0029] The composite catalyst is placed in a fixed bed reactor, and a mixed gas of carbon dioxide and hydrogen and a dimethylamine solution are introduced into the fixed bed reactor to perform a catalytic reaction to obtain DMF.

[0030] The present invention provides a composite catalyst, comprising a molecular sieve and copper-containing particles embedded in the molecular sieve, wherein the copper-containing particles include copper metal particles and cuprous oxide particles. In the present invention, the molecular sieve has a confining effect and can inhibit the agglomeration and migration of metal nanoparticles (copper-containing particles), thereby maintaining the stability of the composite catalyst. The catalyst provided by the present invention is used to catalyze the hydrogenation of CO2 to prepare DMF with high selectivity and yield, and the composite catalyst provided by the present invention has excellent catalytic stability, and still has good selectivity and yield after continuous catalytic operation for 500 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The graph is a graph showing the selectivity and yield of DMF prepared by catalyzing CO2 hydrogenation at different catalytic times using the composite catalyst prepared in Example 1. DETAILED DESCRIPTION

[0032] The present invention provides a composite catalyst, comprising a molecular sieve and copper-containing particles embedded in the molecular sieve, wherein the copper-containing particles include copper metal particles and cuprous oxide particles. In the present invention, the silicon-aluminum ratio of the molecular sieve is preferably 20 to 100:1, more preferably 30 to 80:1.

[0033] In the present invention, the mass percentage of the copper-containing particles in the composite catalyst is preferably 2 to 15%, more preferably 5 to 10%. In the present invention, the copper metal particles and cuprous oxide particles act as active sites.

[0034] The composite catalyst provided by the invention has the characteristics of high catalytic activity, good selectivity and long service life.

[0035] The present invention also provides a method for preparing the composite catalyst described in the above technical solution, comprising the following steps:

[0036] Mixing a copper-based metal organic framework compound, a silicon source and a first solvent to obtain a sol-gel;

[0037] The sol-gel is aged and then dried to obtain a MOF / SiO2 composite;

[0038] The MOF / SiO2 composite, aluminum source, template, alkaline substance and second solvent are mixed and then subjected to hydrothermal crystallization, calcination and reduction treatment in sequence to obtain the composite catalyst.

[0039] The present invention mixes a copper-based metal organic framework compound, a silicon source and a first solvent to obtain a sol-gel. In the present invention, the copper-based metal organic framework compound is preferably a Cu3(BTC)2 metal organic framework compound. In the present invention, the preparation method of the Cu3(BTC)2 metal organic framework compound preferably comprises the following steps:

[0040] The copper source and trimesic acid are dissolved in a solvent to carry out a hydrothermal reaction to obtain the Cu3(BTC)2 metal organic framework compound.

[0041] In the present invention, the copper source is preferably copper nitrate and / or copper acetate, more preferably copper nitrate or copper acetate; the copper nitrate is preferably copper nitrate trihydrate, and the copper acetate is preferably copper acetate monohydrate. In the present invention, the solvent is preferably any one or two of water, methanol, ethanol and N,N-dimethylformamide, more preferably ethanol or N,N-dimethylformamide. In the present invention, the water is preferably distilled water, and the ethanol is preferably anhydrous ethanol. In the present invention, the mass ratio of the copper source to trimesic acid is preferably 1.3-2.0:1-1.2, more preferably 1.5-1.82:1.05; the mass ratio of the copper source to the volume ratio of the solvent is preferably 1.3-1.7g:7-9mL, more preferably 1.5g:8mL. In the present invention, the dissolution preferably includes stirring and ultrasonic treatment performed in sequence; the stirring time is preferably 15-25min, more preferably 20min; the ultrasonic time is preferably 25-35min, more preferably 30min. The present invention has no special limitation on the stirring speed and ultrasonic power, as long as the dissolution is complete.

[0042] In the present invention, the temperature of the hydrothermal reaction is preferably 30 to 150° C., more preferably 60 to 120° C.; the time of the hydrothermal reaction is preferably 8 to 72 h, more preferably 10 to 65 h.

[0043] In the present invention, after the hydrothermal reaction, the method preferably further includes: filtering the system after the hydrothermal reaction; washing the filter cake obtained by filtration; and drying the washed filter cake to obtain the Cu3(BTC)2 metal organic framework compound. The present invention has no special requirements for the filtration, and the conventional method in the art can be used. In the present invention, the washing solvent is preferably anhydrous ethanol or N,N-dimethylformamide; the number of washings is preferably 3 to 5 times. In the present invention, the drying is preferably drying, and the drying temperature is preferably 40 to 80°C, more preferably 50 to 60°C; the drying time is preferably 2 to 12 hours, more preferably 5 to 8 hours.

[0044] In the present invention, the silicon source preferably includes organic silicate, silica sol, water glass or white carbon black, and more preferably organic silicate. In the present invention, the organic silicate is preferably one or more of methyl orthosilicate, ethyl orthosilicate and propyl orthosilicate, and more preferably ethyl orthosilicate or propyl orthosilicate. In the present invention, when the organic silicate includes two or more of the above-mentioned specific substances, there is no special requirement for the ratio of the specific substances, and any ratio can be used.

[0045] In the present invention, the mass ratio of the copper-based metal organic framework compound to the silicon source is preferably 1:3-26, more preferably 1:5-20.

[0046] In the present invention, the first solvent is preferably a mixed solvent of water and an organic solvent; the water is preferably distilled water; the organic solvent is preferably one or more of methanol, ethanol, n-propanol and 1,4-dioxane, more preferably ethanol. In the present invention, the ethanol is preferably anhydrous ethanol. In the present invention, the mass ratio of water to the organic solvent is preferably 1:1 to 4, more preferably 1:1.5 to 2.8. In the present invention, the mass ratio of the copper-based metal organic framework compound to water is preferably 15 to 60:100, more preferably 22 to 30:100, and further preferably 25:100.

[0047] In the present invention, the temperature for mixing the copper-based metal organic framework compound, the silicon source and the first solvent is preferably 45 to 85° C., more preferably 50 to 80° C.; the time for mixing the copper-based metal organic framework compound, the silicon source and the first solvent is preferably 1 to 3 hours, more preferably 2 to 3 hours. The present invention preferably uses a water bath to provide the required temperature for mixing.

[0048] After obtaining the sol-gel, the present invention ages the sol-gel and then dries it to obtain a MOF / SiO2 composite. In the present invention, the aging temperature is preferably room temperature, the room temperature is preferably 20 to 35° C., more preferably 25 to 30° C.; the aging time is preferably 12 to 30 hours, more preferably 18 to 24 hours.

[0049] In the present invention, the drying is preferably oven drying, and the oven drying temperature is preferably 80 to 140° C., more preferably 100 to 120° C.; the oven drying time is preferably 2 to 12 hours, more preferably 6 to 8 hours.

[0050] In the present invention, SiO2 in the MOF / SiO2 composite provides a silicon source for subsequent hydrothermal crystallization.

[0051] After obtaining the MOF / SiO2 composite, the present invention mixes the MOF / SiO2 composite, an aluminum source, a template, an alkaline substance and a second solvent, and then sequentially performs hydrothermal crystallization, calcination and reduction treatment to obtain the composite catalyst. In the present invention, the mixing preferably includes the following steps:

[0052] The MOF / SiO2 composite, the aluminum source and the second solvent are first mixed to obtain a first mixed solution;

[0053] The first mixed solution and the template are mixed for a second time to obtain a second mixed solution;

[0054] The second mixed solution and the alkaline substance are mixed for the third time to obtain a mixed solution.

[0055] The present invention first mixes a MOF / SiO2 complex, an aluminum source and a second solvent to obtain a first mixed solution. In the present invention, the aluminum source is preferably Al(NO3)3·9H2O, pseudo-boehmite, aluminum sulfate or sodium aluminate, and more preferably Al(NO3)3·9H2O. In the present invention, the mass ratio of the aluminum source to SiO2 in the MOF / SiO2 complex is preferably 1:5-10, and more preferably 1:6-8.

[0056] In the present invention, the second solvent is preferably a mixed solvent of ethanol and water. In the present invention, the ethanol is preferably anhydrous ethanol, and the water is preferably distilled water. In the present invention, the mass ratio of the ethanol to the water is preferably 40 to 80:50 to 100, more preferably 60:65 to 75. In the present invention, the mass ratio of the aluminum source to the ethanol is preferably 1:40 to 80, more preferably 1:60 to 80.

[0057] In the present invention, the first mixing is preferably performed under stirring conditions, and the stirring time is preferably 0.4 to 0.6 hours, more preferably 0.5 hours. The present invention has no special requirements on the stirring speed, as long as the mixing is uniform.

[0058] After obtaining the first mixed solution, the present invention secondly mixes the first mixed solution and the template agent to obtain a second mixed solution. In the present invention, the template agent is preferably tetrapropylammonium hydroxide (TPAOH), tetrapropylammonium chloride, tetraethylammonium hydroxide or tetrabutylammonium hydroxide, more preferably tetrapropylammonium hydroxide. In the present invention, the mass ratio of the aluminum source to the template agent is preferably 1:5 to 10, more preferably 1:6 to 8.

[0059] In the present invention, the second mixing is preferably carried out under stirring conditions, and the stirring time is preferably 5 to 7 hours, more preferably 6 hours. The present invention has no special requirements on the stirring speed, as long as it can be mixed evenly.

[0060] After obtaining the second mixed solution, the present invention thirdly mixes the second mixed solution with an alkaline substance to obtain a mixed solution. In the present invention, the alkaline substance is preferably ammonia monohydrate. In the present invention, the mass ratio of the aluminum source to the alkaline substance is preferably 1:50 to 100, more preferably 1:60 to 75.

[0061] In the present invention, the third mixing is preferably carried out under stirring conditions, and the stirring time is preferably 0.4 to 0.6 hours, more preferably 0.5 hours. The present invention has no special requirements on the stirring speed, as long as it can be mixed evenly.

[0062] In the present invention, the temperature of the hydrothermal crystallization is preferably 150-200° C., more preferably 160-180° C.; the time of the hydrothermal crystallization is preferably 1-5 days, more preferably 2-3 days.

[0063] In the present invention, after the hydrothermal crystallization, it is preferred that the following steps are further included: cooling the system after the hydrothermal crystallization to room temperature and filtering, washing and drying the filtered solid. In the present invention, the room temperature is preferably 20-35°C, more preferably 25-30°C. The present invention has no special requirements for the cooling method, as long as the required temperature can be reached. The present invention has no special requirements for the filtration, and the conventional method in the art can be adopted. In the present invention, the washing includes water washing and ethanol washing in sequence; the water used for the water washing is preferably deionized water. In the present invention, the number of water washings is preferably 3-5 times, and the number of ethanol washings is preferably 3-5 times. In the present invention, the drying is preferably drying, and the drying temperature is preferably 100-140°C, more preferably 110-120°C; the drying time is preferably 10-14h, more preferably 12-13h.

[0064] In the present invention, the calcination temperature is preferably 500-650° C., more preferably 550-600° C.; the calcination time is preferably 1-5 h, more preferably 2-3 h.

[0065] In the present invention, the reduction treatment is preferably carried out in a reducing atmosphere; the reducing atmosphere is preferably a mixed gas of hydrogen and nitrogen, and the volume percentage of hydrogen in the mixed gas is preferably 4-6%, more preferably 5%. In the present invention, the temperature of the reduction reaction is preferably 300-550°C, more preferably 350-450°C; the time of the reduction reaction is preferably 2-5h, more preferably 2-3h.

[0066] The present invention also provides the use of the composite catalyst described in the above technical solution or the composite catalyst prepared by the preparation method described in the above technical solution in catalyzing CO2 hydrogenation to prepare DMF.

[0067] The present invention also provides a method for preparing DMF by catalyzing CO2 hydrogenation using the composite catalyst described in the above technical solution or the composite catalyst prepared by the preparation method described in the above technical solution, comprising the following steps:

[0068] The composite catalyst is placed in a fixed bed reactor, and a mixed gas of carbon dioxide and hydrogen and a dimethylamine solution are introduced into the fixed bed reactor to perform a catalytic reaction to obtain DMF.

[0069] In the present invention, the molar ratio of carbon dioxide to hydrogen in the mixture of carbon dioxide and hydrogen is preferably 1-3:1-3, more preferably 1-2:1-2, specifically 1:1, 1:2, 2:1 or 3:1. In the present invention, the volume space velocity of the mixture of carbon dioxide and hydrogen is preferably 200-4000 h / min. -1 , more preferably 500 to 1500 hours -1 In the present invention, the dimethylamine solution is preferably a dimethylamine methanol solution; the mass concentration of the dimethylamine solution is preferably 45-55%, more preferably 50%; the mass space velocity of the dimethylamine solution is preferably 0.2-6.0h -1 , more preferably 0.5 to 3 hours -1 .

[0070] In the present invention, the temperature of the catalytic reaction is preferably 130 to 250° C., more preferably 140 to 230° C.; the pressure of the catalytic reaction is preferably 2 to 8 MPa, more preferably 3 to 6 MPa.

[0071] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0072] Example 1

[0073] 1.5 g of copper acetate monohydrate and 1.05 g of trimesic acid were dissolved in 8 mL of anhydrous ethanol, stirred for 20 min, ultrasonicated for 30 min, and then hydrothermally reacted at 60°C for 48 h. After cooling, the filtered cake was washed three times with anhydrous ethanol, and the washed filter cake was placed in an oven at 50°C and dried for 8 h to obtain a copper-based metal organic framework compound [Cu3(BTC)2]-1.

[0074] 5.0 g [Cu3(BTC)2]-1, 22.0 g distilled water, 37.0 g anhydrous ethanol and 28.5 g ethyl orthosilicate were stirred in a water bath at 70 °C for 2 h to form a sol-gel;

[0075] The sol-gel was aged at room temperature for 24 h and then dried in an oven at 120 °C for 12 h to obtain a MOF / SiO2 composite, which was designated as Cu / SiO2-1.

[0076] 0.8g Cu / SiO2-1, 0.1g Al(NO3)3·9H2O, 7.5g distilled water and 6.0g ethanol were stirred for 0.5h and then mixed with 0.8g tetrapropylammonium hydroxide and stirred for 6h at room temperature; then, 7.5g NH3·H2O was added to the mixture and stirred for 0.5h at room temperature; the obtained mixed solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, hydrothermally crystallized at 180°C for 3 days, filtered after cooling to room temperature, and the filtered solid was washed 3 times with deionized water and then washed 3 times with ethanol; the washed solid was dried at 120°C for 12h, calcined in air at 550°C in a muffle furnace for 3h, and reduced at 350°C in a mixed atmosphere of H2 and N2 with a hydrogen volume percentage of 5% for 3h to obtain a composite catalyst, recorded as Cu@molecular sieve-1.

[0077] Example 2

[0078] 1.82 g of copper nitrate trihydrate and 1.05 g of trimesic acid were dissolved in 8 mL of anhydrous ethanol, stirred for 20 min, ultrasonicated for 30 min, and then hydrothermally reacted at 10°C for 24 h. After cooling, the filtered cake was washed three times with anhydrous ethanol, and the washed filter cake was placed in an oven at 60°C and dried for 6 h to obtain a copper-based metal organic framework compound [Cu3(BTC)2]-2.

[0079] 5.0 g [Cu3(BTC)2]-2, 22.0 g distilled water, 37.0 g anhydrous ethanol and 28.5 g ethyl orthosilicate were stirred in a water bath at 50 °C for 3 h to form a sol-gel;

[0080] The sol-gel was aged at room temperature for 24 h and then dried in an oven at 100 °C for 12 h to obtain a MOF / SiO2 composite, which was designated as Cu / SiO2-2.

[0081] 0.6g Cu / SiO2-2, 0.1g Al(NO3)3·9H2O, 5.0g distilled water and 4.0g ethanol were stirred for 0.5h and then mixed with 0.6g tetrapropylammonium hydroxide and stirred for 6h at room temperature; then, 7.5g NH3·H2O was added to the mixture and stirred for 0.5h at room temperature; the obtained mixed solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, hydrothermally crystallized at 150°C for 5 days, filtered after cooling to room temperature, and the filtered solid was washed 3 times with deionized water and then washed 3 times with ethanol; the washed solid was dried at 120°C for 12h, calcined in air at 600°C in a muffle furnace for 3h, and reduced at 450°C in a mixed atmosphere of H2 and N2 with a hydrogen volume percentage of 5% for 2h to obtain a composite catalyst, recorded as Cu@molecular sieve-2.

[0082] Example 3

[0083] 1.5 g of copper acetate monohydrate and 1.05 g of trimesic acid were dissolved in 8 mL of anhydrous ethanol, stirred for 20 min, ultrasonicated for 30 min, and then hydrothermally reacted at 120° C. for 12 h. After cooling, the filtered cake was washed three times with anhydrous ethanol, and the washed filter cake was placed in an oven at 80° C. and dried for 3 h to obtain a copper-based metal organic framework compound [Cu3(BTC)2]-3.

[0084] 5.0 g [Cu3(BTC)2]-3, 20.0 g distilled water, 40.0 g anhydrous ethanol and 36.2 g propyl orthosilicate were stirred in a water bath at 80 °C for 2 h to form a sol-gel;

[0085] The sol-gel was aged at room temperature for 24 h and then dried in an oven at 80 °C for 12 h to obtain a MOF / SiO2 composite, which was designated as Cu / SiO2-3.

[0086] 1.0g Cu / SiO2-3, 0.1g Al(NO3)3·9H2O, 10.0g distilled water and 8.0g ethanol were stirred for 0.5h and then mixed with 1.0g tetrapropylammonium hydroxide and stirred for 6h at room temperature; then, 10.0g NH3·H2O was added to the mixture and stirred for 0.5h at room temperature; the obtained mixed solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, hydrothermally crystallized at 180°C for 2 days, filtered after cooling to room temperature, and the filtered solid was washed 3 times with deionized water and then washed 3 times with ethanol; the washed solid was dried at 120°C for 12h, calcined in air at 500°C in a muffle furnace for 5h, and reduced at 450°C in a mixed atmosphere of H2 and N2 with a hydrogen volume percentage of 5% for 2h to obtain a composite catalyst, recorded as Cu@molecular sieve-3.

[0087] Example 4

[0088] 1.5 g of copper acetate monohydrate and 1.05 g of trimesic acid were dissolved in 8 mL of N,N-dimethylformamide, stirred for 20 min, ultrasonicated for 30 min, and then hydrothermally reacted at 150°C for 8 h. After cooling, the mixture was filtered and the filter cake was washed three times with N,N-dimethylformamide. The washed filter cake was dried in an oven at 80°C for 5 h to obtain a copper-based metal organic framework compound [Cu3(BTC)2]-4.

[0089] 5.0 g [Cu3(BTC)2]-4, 20.0 g distilled water, 30.0 g anhydrous ethanol and 28.5 g ethyl orthosilicate were stirred in a water bath at 70 °C for 2 h to form a sol-gel;

[0090] The sol-gel was aged at room temperature for 24 h and then dried in an oven at 140 °C for 6 h to obtain a MOF / SiO2 composite, which was designated as Cu / SiO2-4.

[0091] 0.7g Cu / SiO2-1, 0.1g Al(NO3)3·9H2O, 7.0g distilled water and 6.0g ethanol were stirred for 0.5h and then mixed with 0.7g tetrapropylammonium hydroxide and stirred for 6h at room temperature; then, 7.5g NH3·H2O was added to the mixture and stirred for 0.5h at room temperature; the obtained mixed solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, hydrothermally crystallized at 180°C for 3 days, filtered after cooling to room temperature, and the filtered solid was washed 3 times with deionized water and then washed 3 times with ethanol; the washed solid was dried at 120°C for 12h, calcined in air at 650°C in a muffle furnace for 3h, and reduced at 350°C in a mixed atmosphere of H2 and N2 with a hydrogen volume percentage of 5% for 3h to obtain a composite catalyst, recorded as Cu@molecular sieve-4.

[0092] Example 5

[0093] 1.5 g of copper acetate monohydrate and 1.05 g of trimesic acid were dissolved in 8 mL of anhydrous ethanol, stirred for 20 min, ultrasonicated for 30 min, and then hydrothermally reacted at 80 ° C for 36 h. After cooling, the filtered cake was washed three times with anhydrous ethanol, and the washed filter cake was placed in an oven at 60 ° C for 5 h to obtain a copper-based metal organic framework compound [Cu3(BTC)2]-5;

[0094] 5.0 g [Cu3(BTC)2]-5, 20.0 g distilled water, 60.0 g anhydrous ethanol and 28.5 g ethyl orthosilicate were stirred in a water bath at 70 °C for 2 h to form a sol-gel;

[0095] The sol-gel was aged at room temperature for 18 h and then dried in an oven at 100 °C for 8 h to obtain a MOF / SiO2 composite, which was designated as Cu / SiO2-5.

[0096] 0.6g Cu / SiO2-5, 0.1g Al(NO3)3·9H2O, 6.5g distilled water and 6.0g ethanol were stirred for 0.5h and then mixed with 0.6g tetrapropylammonium hydroxide and stirred for 6h at room temperature; then, 6.0g NH3·H2O was added to the mixture and stirred for 0.5h at room temperature; the obtained mixed solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, hydrothermally crystallized at 180°C for 3 days, filtered after cooling to room temperature, and the filtered solid was washed 3 times with deionized water and then washed 3 times with ethanol; the washed solid was dried at 120°C for 12h, calcined in air at 550°C in a muffle furnace for 3h, and reduced at 300°C in a mixed atmosphere of H2 and N2 with a hydrogen volume percentage of 5% for 5h to obtain a composite catalyst, recorded as Cu@molecular sieve-1.

[0097] The composite catalysts prepared in Examples 1 to 5 were evaluated in a fixed bed microreactor; the composite catalyst was used to catalyze the hydrogenation of CO2 to prepare DMF. The specific conditions were: the composite catalyst loading was 3.0 g, a mixture of CO2 and H2 with a molar ratio of 1:1 was used as the reaction gas, and the volumetric space velocity of the mixture was 1000 h -1 ; Using a 50% dimethylamine methanol solution as the reaction solution, the mass space velocity of the dimethylamine methanol solution is 1.5h -1 The temperature of the catalytic reaction was 160°C, the pressure was 6 MPa (gauge pressure), and the reaction time was 20 hours. After the reaction, samples were taken and the products were quantitatively analyzed in gas chromatography. The results are shown in Table 1.

[0098] Table 1 Conversion rate and selectivity of composite catalysts used in catalytic CO2 hydrogenation to prepare DMF in Examples 1 to 5

[0099] Example Conversion rate (%) Selectivity (%) Example 1 62 98 Example 2 55 96 Example 3 57 95 Example 4 60 97 Example 5 56 98

[0100] According to the above evaluation method, the composite catalyst prepared in Example 1 was used to catalyze the hydrogenation of CO2 to prepare DMF under different conditions. The reaction conditions and reaction results are listed in Table 2.

[0101] Table 2 The composite catalyst of Example 1 catalyzes CO2 hydrogenation to prepare DMF under different conditions

[0102]

[0103]

[0104] It can be seen from Table 1 and Table 2 that the composite catalyst provided by the present invention can prepare DMF by catalytic hydrogenation using carbon dioxide as a raw material, and has a high conversion rate and selectivity.

[0105] According to the above evaluation method, the Cu@molecular sieve-1 composite catalyst prepared in Example 1 was used to catalyze the hydrogenation of CO2 to prepare DMF. The reaction conditions were: reaction temperature of 180°C, pressure of 6 MPa, molar ratio of CO2 to H2 of 1:1, and volumetric space velocity of the mixture of CO2 and H2 of 1000 h -1 The mass space velocity of a 50% dimethylamine methanol solution is 1.5 h -1 The yield and selectivity of DMF at different catalytic reaction times were detected by gas chromatography, and the results are listed in Table 3.

[0106] Table 3 Selectivity and yield of DMF of the composite catalyst of Example 1 at different catalytic times

[0107]

[0108]

[0109] According to Table 3, the selectivity and productivity curves of preparing DMF by catalytic CO2 hydrogenation at different catalytic times are plotted, as shown in FIG. Figure 1 shown.

[0110] Combining Table 3 and Figure 1 It can be seen that the composite catalyst provided by the present invention has a long service life, and still has good conversion rate and selectivity after the reaction is run for 500 hours. The composite catalyst provided by the present invention has good catalytic stability.

[0111] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A composite catalyst, characterized in that: The invention comprises a molecular sieve and copper-containing particles embedded in the molecular sieve, wherein the copper-containing particles comprise copper metal particles and cuprous oxide particles.

2. The composite catalyst according to claim 1, characterized in that: The mass percentage of the copper-containing particles in the composite catalyst is 2-15%.

3. The composite catalyst according to claim 1, characterized in that: The silicon-aluminum ratio of the molecular sieve is 20-100:

1.

4. The method for preparing the composite catalyst according to any one of claims 1 to 3, comprising the following steps: Mixing a copper-based metal organic framework compound, a silicon source and a first solvent to obtain a sol-gel; The sol-gel is aged and then dried to obtain a MOF / SiO2 composite; The MOF / SiO2 composite, aluminum source, template, alkaline substance and second solvent are mixed and then subjected to hydrothermal crystallization, calcination and reduction treatment in sequence to obtain the composite catalyst.

5. The preparation method according to claim 4, characterized in that: The copper-based metal organic framework compound is a Cu3(BTC)2 metal organic framework compound; The silicon source includes organic silicate, silica sol, water glass or white carbon black; The mass ratio of the copper-based metal organic framework compound to the silicon source is 1:3-26; The first solvent is a mixed solvent of water and an organic solvent, and the mass ratio of water to the organic solvent is 1:1-4; The mass ratio of the copper-based metal organic framework compound to water is 15 to 60:100; The mixing temperature is 45-85° C. and the mixing time is 1-3 hours.

6. The preparation method according to claim 4, characterized in that: The aging time is 12 to 30 hours; The drying is oven drying, the oven drying temperature is 80 to 140° C., and the oven drying time is 2 to 12 hours.

7. The preparation method according to claim 4, characterized in that: The aluminum source is Al(NO3)3·9H2O, pseudo-boehmite, aluminum sulfate or sodium aluminate; the mass ratio of the aluminum source to SiO2 in the MOF / SiO2 composite is 1:5-10; The template agent is tetrapropylammonium hydroxide, tetrapropylammonium chloride, tetraethylammonium hydroxide or tetrabutylammonium hydroxide; the mass ratio of the aluminum source to the template agent is 1:5-10; The alkaline substance is ammonia monohydrate; The second solvent is a mixed solvent of ethanol and water; the mass ratio of the ethanol to water is 40-80:50-100.

8. The preparation method according to claim 4 or 7, characterized in that: The hydrothermal crystallization temperature is 150-200°C and the time is 1-5 days; The calcination temperature is 500-650°C and the calcination time is 1-5h; The reduction treatment is to carry out a reduction reaction in a reducing atmosphere; the temperature of the reduction reaction is 300 to 550° C., and the time of the reduction reaction is 2 to 5 hours.

9. Use of the composite catalyst according to any one of claims 1 to 3 or the composite catalyst prepared by the preparation method according to any one of claims 4 to 8 in catalyzing CO2 hydrogenation to prepare DMF.

10. A method for preparing DMF by catalyzing CO2 hydrogenation using the composite catalyst according to any one of claims 1 to 3 or the composite catalyst prepared by the preparation method according to any one of claims 4 to 8, comprising the following steps: The composite catalyst is placed in a fixed bed reactor, and a mixed gas of carbon dioxide and hydrogen and a dimethylamine solution are introduced into the fixed bed reactor to perform a catalytic reaction to obtain DMF.